PENGARUH TERAPI SOCIAL SKILLS TRAINING TERHADAP HARGA DIRI DAN PERILAKU AGRESIF REMAJA DI SMK PERTIWI MOJOKERTO DENGAN PENDEKATAN MODEL INTERPERSONAL PEPLAU - Nurul Mawaddah* Ahsan** Lilik Supriati*** (Universitas Muhammadiyah Jember, 2016)
Adolescence is a developmental period marked by physical changes, cognitive and social that can contribute to the emergence of social problems due to the lack of social skills. Therefore we need therapy social skills training to improve their social competence so that the adolescent self-esteem increased in order to build and maintain positive relationships with the surrounding environment and friends. This study aims to determine the effect of social skills therapy trainning to self-esteem and aggressive behavior of adolescents with interpersonal models approach Peplau. The research design is quasi-experimental pre-post test with control group. The sampling technique isProportionate Stratified Random Sampling with 26 samples obtained for the treatment group and 26 samples for the control group. the results showed that the therapy social skills training and counseling can improve self -esteem and decrease aggressive behavior. the results showed an increase in self -esteem and a decrease in aggressive behavior in the group receiving social skills trainingtherapy were significantly higher (pvalue 0.05) compared with the control group.In addition there was no association found between self -esteem and aggressive behavior of adolescents. Peplau approach will make it easier to interact with aggressive adolescents so that therapy is more effective SST